KUBUS SEBAGAI IDE DASAR PENCIPTAAN MEJA LAPTOP DENGAN ORNAMEN MANTINGAN SEBAGAI UNSUR HIAS - Andrik Kurnianto; Jati Widagdo (SULUH: Jurnal Seni Desain Budaya, 2020)
The rapid development of technology, industry and design in the current era of globalization shows that the quality of human resources is increasing. Technological progress can be seen in the various changes in mindset, innovation and increasingly advanced human life styles. furniture needs needed to support activities. The table is a piece of furniture that is needed to support comfort when operating a laptop. In addition to the convenience of a simple table shape, the function of the table is maximized, one of which is a cube. The simplicity of the cube shape adds practical value and beauty to space.This research produces a laptop desk that is comfortable, not large, and can be used to put things in. The shape of the cube and the provision of ornaments of the mantingan mosque as a decorative element to form the aesthetics of the laptop table